Reversed thermo-switchable molecular sieving membranes composed of two-dimensional metal-organic nanosheets for gas separation - Xuerui Wang (Nature Portfolio, 2017)
Reducing membrane thickness to nanometre scale should increase the throughput of gas separation sieves. Here, the authors report a sieving membrane composed of two-dimensional metal-organic framework nanosheets, exhibiting both high permeation flux and thermally switchable behaviour.